Evaluasi Pelaksanaan Pemenuhan Kewajiban Pajak Orang Pribadi Tertentu Pada Kantor Pelayanan Pajak Pratama Pondok Aren - Ambarwati Ambarwati (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Self assessment system of Indonesian taxation demands high level of taxpayers’ awareness and compliance in fulfilling tax liabilities in order to increase state revenue from taxation sector. The level of compliance could be increased through providing better service quality by the taxation office, which includes safety, comfort, and quick services, as well as law enforcement. This study is to determine whether there is influence understanding of tax laws, the tax rate and the principle of fairness on tax compliance, Micro, Small and Medium Enterprises after the enactment of Government Regulation No. 46 Year 2013. Information and Communication Technology Utilization is influential to or delivered an impact on the increase of taxpayers’ obedience. this study uses descriptive types of qualitative research. Data has obtained by the interview for extensification and counseling, practitioners and tax academy as well as Business Development Service (BDS) participants in Kantor Pelayanan Pajak Pratama Pondok Aren. The result of this research indicates that the taxpayers’ awareness does not significantly influence on taxpayers’ compliance. Knowledge of taxation significantly affects on taxpayers’ compliance. Taxpayers’ attitudes significantly affect on taxpayers’ compliance.